Process of Confiscation of Assets Proceeding from Crime of Selling Narcotics Carried Out by the National Narcotics Agency of Aceh Province - Robby Dian; Kartina Pakpahan; Elvira Fitriyani Pakpahan (JUSTICES: Journal of Law, 2024)
The background of this research is that disclosing the source of funds from the sale of narcotics is very important because wealth is the weakest point of crime with the principle of criminology which states that money is the blood of crime or what is more often known as Money is the blood of the crime. Funds from crime, in this case narcotics, are often reused to grow and finance the crime itself so that the crime becomes bigger and better organized, which results in this case being the case that narcotics crime itself becomes an organized crime. The result of this research is the process of confiscation of assets resulting from sales crimes. Narcotics carried out by the Aceh BNNP is carried out through a mapping stage process. The next stage is the confiscation stage after receiving a decision that has permanent legal requirements, where the assets are in the form of cash, which is immediately deposited into the state treasury by the Prosecutor's Office as non-tax state revenue (PNBP). Meanwhile, assets in the form of securities, movable or not, tangible or not, are managed by the Ministry of Finance. Constraints faced by the Aceh BNNP in the process of returning assets from the sale of narcotics are the limited capacity of human resources investigating money laundering at the Aceh BNNP and the limited research and inquiry budget. The crime of money laundering, the implementation of MLA, takes a long time and is not optimal due to clashes between legal systems. Prevention efforts carried out by the Aceh BNNP in dealing with Narcotics Crime are through the Hard Power Approach, Soft Power Approach, Smart Power Approach and Co-Operation.